Clinicoepidemiological study of post burn contractures at a tertiary care centre in western India - Mehta, Milind A.; Ranjan, Vikrant; Kulkarni, Abhishek K.; Sarwade, Pradnya (International Surgery Journal, 2019)
Background: Burn injuries are one of the commonest form of trauma globally with long term consequences in the form of contractures. The management takes a troll of time, money and stress, despite that the agony remains with the patient only. We intended to study the clinicoepidemiopathological aspects of post burn contractures for a better understanding and management purpose. Methods: This study was conducted from October 2014 to February 2017 in a tertiary care hospital in western India and includes 51 patients. Results: In this study, we observed that the mean age of patients was 21.7 years and females formed 51% of the patient pool. Most of the patients came from a rural background with a mean distance of 77.72 kilometres from the treating hospital. Flame burns contributed to 78% of the cases, with hand (35.7%) being the most commonly involved area, 52.9% patients did not receive splinting or physiotherapy at the initial treatment of burns. Most cases were treated by split skin grafting (64.2%) and the most common complication seen in our study was infection, noted in 15.7% of cases whereas recurrence was seen in only one patient. Conclusions: We observed that young adults were the predominant group of patients with a slight female preponderance. Factors like increased distance from the treating hospital, rural background of patients, poor healthcare facilities with poor rehabilitative facilities and irregular follow up of patients contributed to increased incidence of post burn contractures. We also noted that majority cases can be treated by contracture release with split skin grafting without major complications.